Teachers' Perceptions of the Relevance of Islamic Studies Curriculum Content to Values and Moral Development in Nigeria Secondary Schools - Kabir, Asmau Imam Abdul (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to analyze teachers' perceptions of the relevance of Islamic studies curriculum content to values and moral development. The study participants were 65 Islamic religious study teachers from public and private schools in Ilorin, Kwara state, Nigeria, who were selected by simple random selection. The data were collected using a five-point Likert scale. The teacher's perception of Islamic studies for moral development was analyzed using SPSS. The data were analyzed using descriptive statistics such as Percentages, Mean scores, and Standard Deviation. The significant outcome indicates that the current Islamic studies curriculum contents, textbooks, and syllabus are inadequate for teaching Islamic values and developing moral and ethical character among the learners. The study, therefore, recommended, among others, improving the Islamic education curriculum content, syllabus, and textbooks to educate learners, inculcate Islamic religious values and moral and ethical character, and present Allah SWT as the most merciful as the only one worthy of worship.